A general framework for diagnosis of discrete event systems subject to sensor failures - Takai, Shigemasa (Automatica (Oxford), 2021)
We consider a failure diagnosis problem for discrete event systems in the presence of sensor failures. In most existing works on failure diagnosis subject to sensor failures, intermittent sensor failures and permanent ones are dealt with separately. The case where any event in a subset of the observable event set possibly becomes unobservable intermittently or permanently can be modeled in the existing framework for intermittent sensor failures. However, for example, the case where at most n′ events in a set of n(>n′) observable events become unobservable cannot be dealt with. The purpose of this paper is to develop a general framework where the diagnosis problem can be addressed in the presence of both intermittent and permanent sensor failures. We introduce a new notion of diagnosability subject to sensor failures and present a procedure of online diagnosis in the general framework. Then, we present how to verify the diagnosability property. For a diagnosable system subject to sensor failures, we compute the delay bound within which the occurrence of any failure string can be detected.